Papers - Increasing the Extraction of Oil - Modern Practice in Water-flooding of Oil Sands in the Bradford and Allegany Fields (With Discussion) - Paul D. Torrey (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1930)
The water-flooding of oil sands has been widely practiced for many years in the Bradford and Allegany fields. Its effect upon the production of these fields has been almost phenomenal. In 1907 their estimated production was 3500 bbl. per day; in December, 1929, the combined production is estimated at 33,000 bbl. per day, an increase of almost 1000 per cent. in 22 years. This increase in production is directly attributable to the successful application of water-flooding, which has transformed the fields that were rapidly approaching abandonment into one of the most actively operated regions associated with the petroleum industry, and has made them important factors in the production of Pennsylvania Grade crude oil. The writer is indebted to many companies for information included in this paper. He is particularly grateful to the Sloan and Zook Co., the Petroleum Reclamation Co., George Bovaird, Jr., and the Associated Producers Co., of Bradford, Pa., who have generously made available much valuable data. Owing to the frequently competitive and confidential nature of property purchases, it has not always been possible to make specific reference to individual wells or properties; but wherever feasible, specific references have been made. Economic Factors The successful application of water-flooding for increasing the recovery of oil has been almost confined to the Bradford and Allegany fields. This has been due not only to legal restrictions in other fields and to very favorable sand conditions in the Bradford-Allegany region, but also to certain economic factors which are worthy of consideration. There has been some alarm regarding the effects of the rapidly increasing production upon the oil market but the writer is inclined to believe that future development can be made sufficiently flexible to meet the demand for this grade of oil. There has been a decided tendency toward consolidation of properties by mergers and purchases and, in addition, many of the individual producers are content to take advantage of floods advancing on their holdings from adjoining properties without developing their own on an intensive scale. Cooperative drilling along